Purification of gas and liquid media by metal-ceramic SHS-filters; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Geyneman A. A.; Goncharov V. D.; Novoselov A. L.; Shchetinkina N. Yu. (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа